2019
DOI: 10.1021/acsomega.9b02388
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Structures of Inclusion Complexes of Amylose with Natural Phenolic Amphiphiles

Abstract: Amylose inclusion complexes were prepared in aqueous solution with the amphiphilic moiety 3-pentadecylphenol via a direct mixing method. Attenuated total reflection Fourier transform infrared spectroscopy as well as differential scanning calorimetry confirmed the formation of amylose inclusion complexes. The morphology of the synthesized complexes is sensitive to temperature, and X-ray data revealed that the inclusion complexes exhibited distinct structures at different temperatures. Small-angle X-ray scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…The shape of the crystals, ED diagrams and unit cell parameters are very similar to those of Vpropan-2-ol crystals (Fig. S6a-c) (Buléon et al, 1990;Nishiyama et al, 2010;Yamashita & Hirai, 1966) and consistent with earlier reports on V-amylose crystallized with different ligands such as thymol, carvacrol (Helbert, 1994), geraniol, fenchone, menthone (Nuessli, Putaux, Le Bail, & Buléon, 2003), linalool, terpineol (Putaux, Cardoso, Morin, Hu, & Dupeyre, 2008), or pentadecylphenol (Kumar & Loos, 2019).…”
Section: Crystal Structuresupporting
confidence: 86%
See 1 more Smart Citation
“…The shape of the crystals, ED diagrams and unit cell parameters are very similar to those of Vpropan-2-ol crystals (Fig. S6a-c) (Buléon et al, 1990;Nishiyama et al, 2010;Yamashita & Hirai, 1966) and consistent with earlier reports on V-amylose crystallized with different ligands such as thymol, carvacrol (Helbert, 1994), geraniol, fenchone, menthone (Nuessli, Putaux, Le Bail, & Buléon, 2003), linalool, terpineol (Putaux, Cardoso, Morin, Hu, & Dupeyre, 2008), or pentadecylphenol (Kumar & Loos, 2019).…”
Section: Crystal Structuresupporting
confidence: 86%
“…This property can find applications, for instance, in the food industry (flavor encapsulation, texturing, etc.) or in pharmacology (vectorization, controlled release) (Carbinatto, Ribeiro, Colnago, Evangelista, & Cury, 2013;Conde-Petit, Escher, & Nuessli, 2006;Kumar & Loos, 2019;Lay Ma, Floros, & Ziegler, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with the crystallinity results showing that the relative crystalline of amylose (67.14 ± 0.67%) was higher than that of the A-L complex (51.46 ± 0.22%). Liu et al (2013) reported that when a host molecule encapsulates a smaller ligand molecule, the original characteristic absorbance peaks of the ligand molecule shifted or disappeared (Kumar & Loos, 2019;Prabu et al, 2015). The spectral characteristics of lycopene (R 1 HC=CR 2 H) at 960 cm -1 disappeared and there was no new absorption peak in the infrared spectra of the A-L complex.…”
Section: D) A-l Complexmentioning
confidence: 99%
“…The resulting inclusion compounds are known under the generic name of “V-amylose”. In these crystals, the guest molecules can be entrapped in the hydrophobic cavity of the amylose helices and/or between them. , This property can be used, for instance, to develop ingredients for functional foods or encapsulate weakly soluble compounds and subsequently release them under controlled conditions. Determining the crystal structure of the complexes is thus crucial to understand such host–guest interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Hexagonal V borneol and V camphor crystals were described as containing close-packed sevenfold helices, and by analogy with the V6 I /V h structure, the allomorph was referred to as V7 I . A V7 II allomorph was characterized for complexes with propan-2-ol, , thymol, carvacrol, menthone, fenchone, linalool, and terpineol, and it has recently been shown that V ibuprofen and V pentadecylphenol were isomorphous complexes. All lamellar crystals are rectangular and yield similar base-plane ED patterns with only minor variations in spot intensities.…”
Section: Introductionmentioning
confidence: 99%